Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00345-014-1476-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adenomectomy versus Eraser laser enucleation of the prostate

Abstract: Laparoscopic adenomectomy and ELEP were equally effective for relieving bladder outflow obstruction and lower urinary tract symptoms. The advantages of ELEP include less blood loss, shorter catheterization times, and shorter hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
6
0
2
Order By: Relevance
“…Umari et al [ 17 ] also reported that four of 45 (8.9%) patients reported transient urinary incontinence following HoLEP, while only one of 81 (1.2%) complained of transient incontinence following RASP. Only one study [ 15 ] evaluated quality of life at 3 and 6 months, showing comparable results ( P = 0.84).
Figure 3.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Umari et al [ 17 ] also reported that four of 45 (8.9%) patients reported transient urinary incontinence following HoLEP, while only one of 81 (1.2%) complained of transient incontinence following RASP. Only one study [ 15 ] evaluated quality of life at 3 and 6 months, showing comparable results ( P = 0.84).
Figure 3.
…”
Section: Resultsmentioning
confidence: 99%
“…For HoLEP, the conventional Gilling technique was used. The summary of the preoperative parameters for the different studies are listed in Table 1 [1, [14][15][16][17][18].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 73 studies after reviewing abstracts and titles, and 6 articles after reading the full text. Finally, 8 studies involving 1,504 patients (492 MISP vs. 1,012 EEP) were included in the present meta-analysis (12)(13)(14)(15)(16)(17)(18)(19). These studies were published between 2015 and 2021.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Among them, one was a prospective study (16), six were retrospective studies (12-15, 18, 19), and one was a prospective randomized study (17). Four studies (12,13,18,19) focused on the comparison of LSP and EEP, three studies (14-16) focused on the comparison of RASP and EEP, and only one study (17) analyzed the comparison of LSP, RASP, and EEP. Additionally, since Fuschi et al (17) reported the comparison of two MISP technologies (LSP and RASP) with EEP, we divided their results into two parts and presented them as Fuschi 2020a (LSP vs. EEP) and Fuschi 2020b (RASP vs. EEP) during data analysis.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%